Analisis Yuridis PERPPU Cipta Kerja No.2 Tahun 2022 Besaran Pesangon Pasca PHK - Arifuddin Muda Harahap; Adella Iragil Sofianti; Cindy Aryanti; Diva Ariza Kesuma; Fauzi Masfa Rizky,; Ibnu Fauzi Bangun; M.Fikri Haekal; M. Rafly; Safira Prima Indira (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
One of the problems for workers in Indonesia is termination of employment (PHK) between workers and employers, in 2020 the government issued Law No. 11 of 2020 concerning work copyright or the omnibus law getting pros and cons from society, of course there are also many people disagree about this work copyright law. Then in 2022 the Government has also officially promulgated Law Number 2 of 2022 Concerning Job Creation which in outline has revised this omnibus law, at least covering 11 sections that have regulated strategic policies, including one of them related employment. This research wants to discuss the comparison of severance pay for employees who have been laid off according to Law no. 2 of 2022 regarding the copyright of this work. The method used in conducting research in this scientific journal is the normative legal method.In Law no. 2 of 2022 regarding this work copyright, workers whose contracts are terminated with less than a year's work period will receive severance pay of 1 month's wages. Those whose duration of work is more than a year, but when it is less than two years will receive 2 months' wages and so on. In addition to severance pay, this Law also regulates the provision of reward money for years of service for employees who have been laid off for working for 3 years or more but less than 6 years, 2 months of wages, at working period of 6 years or more but less than 9 years, 3 months wages and so on. Keywords: employment, layoffs, severance pay